1999
DOI: 10.1088/0964-1726/8/6/310
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber sensors for spacecraft applications

Abstract: Optical fiber sensors offer a number of advantages for spacecraft applications. A principal application is strain sensing for structural health monitoring, shape determination, and spacecraft qualification testing. This paper will review the results of recent work at the Naval Research Laboratory where optical fiber strain sensors have been used on spacecraft structures and ground test hardware. The sensors have been both surface mounted to the structure and embedded in fiber-reinforced polymer composites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…Such findings agree with the compressive strength reductions reported in the FOS studies, which found a range of values from 30 to 70 per cent, depending on FOS orientation, laminate thickness, host composite, etc. ( Jensen et al 1992b;Friebele et al 1999;Shivakumar & Emmanwori 2004;Kousourakis et al 2008). Note that the last column in table 4 indicates the proportion of laminate specimens failed in 'predicted failure mode' (i.e.…”
Section: Compression Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings agree with the compressive strength reductions reported in the FOS studies, which found a range of values from 30 to 70 per cent, depending on FOS orientation, laminate thickness, host composite, etc. ( Jensen et al 1992b;Friebele et al 1999;Shivakumar & Emmanwori 2004;Kousourakis et al 2008). Note that the last column in table 4 indicates the proportion of laminate specimens failed in 'predicted failure mode' (i.e.…”
Section: Compression Test Resultsmentioning
confidence: 99%
“…Jensen and colleagues (1992a,b) are among the pioneers to study the influence upon host composite performance following embedment of FOS with regard to orientation and numbers of FOS. Subsequent researchers concluded that the degradation of material strength and modulus is significantly affected by the optical fibre diameter, the FOS orientation relative to nearest plies and the FOS materials (Friebele et al 1999;Zhou et al 2004;Fernando & Degamber 2006). Apart from modifying the diameter and constituent materials of FOS in order to reduce their influence on resulting performance, it is the resin-rich pocket caused by off-axis FOS embedment that draws the attention of most researchers.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a protection results in inconsistency between the fiber strain and the structural strain. Such discrepancies are neglected in many applications of OFSs by simply assuming that the fiber strain is consistent with the host structural strain (Friebele et al, 1999;Udd, 1995). Such assumption gives acceptable measurement results for the OFSs with long gauge length, in which the peak host strain can be fully transferred into the fiber strain, but cannot provide good measurement strains for short gauge OFSs, for instance, FBG sensors, in which the effect of the bonded fiber length on strain transfer between the fiber and host structure is significant (Galiotis et al, 1984).…”
Section: Strain Transferring Mechanism For Embedded Ofssmentioning
confidence: 99%
“…Typical wavelength changes of FBG written in standard single-mode fiber at 1550 nm region due to mechanical strain and temperature variation are ∼1 pm/με and ∼11 pm/ • C, respectively. Because of its compact size, low optical loss, self-referencing, and wavelength multiplexing capability, FBG sensors have been widely applied in a wide range of condition monitoring applications [9,[15][16][17][18][19]]. …”
Section: Fbg Sensor and Wavelength Interrogation Systemmentioning
confidence: 99%